Image forming apparatus, and image forming method
Patent Information
- Application Number
- JP2023128181
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0007】 <1>に係る発明によれば、転写対向ベルトに接触する表面での押し込み弾性率が35MPa超であるクリーニングブレード、又は転写対向ベルトに接触する表面から200nm以内に存在するF及びSiの総量が、表面から5μm以内に存在するF及びSiの総量に対し75%未満であるクリーニングブレードを備える画像形成装置に比べて、転写対向ベルト表面上でのトナーフィルミングの発生が抑制され、かつクリーニングブレードにおける摩耗が抑制された画像形成装置が提供される。 <2>に係る発明によれば、トナー粒子の表面から800nm以内の領域に存在する離型剤がトナー粒子全体の離型剤の75%未満である画像形成装置に比べて、画像の低温定着性に優れた画像形成装置が提供される。 <3>に係る発明によれば、離型剤の融解温度が75℃超である画像形成装置に比べて、画像の低温定着性に優れた画像形成装置が提供され、離型剤の融解温度が70℃未満である画像形成装置に比べて、転写対向ベルト表面上でのトナーフィルミングの発生が抑制された画像形成装置が提供される。 <4>に係る発明によれば、クリーニングブレードの押し込み弾性率が20MPa未満である画像形成装置に比べて、転写対向ベルトとクリーニングブレードとの接触箇所でのトナーのすり抜けの発生が抑制された画像形成装置が提供され、クリーニングブレードの押し込み弾性率が30MPa超である画像形成装置に比べて、転写対向ベルト表面上でのトナーフィルミングの発生が抑制される画像形成装置が提供される。 <5>に係る発明によれば、転写対向ベルトに接触する表面から200nm以内に存在するF及びSiの総量が、表面から5μm以内に存在するF及びSiの総量に対し85%未満であるクリーニングブレードを備える画像形成装置に比べて、クリーニングブレードの接触部での摩耗が抑制される画像形成装置が提供される。 <6>又は<7>に係る発明によれば、転写対向ベルトに接触する表面に存在するF及びSiの総量が15atm%未満であるクリーニングブレードを備える画像形成装置に比べて、クリーニングブレードの接触部での摩耗が抑制される画像形成装置が提供される。 <8>又は<9>に係る発明によれば、転写対向ベルトに接触する表面から50nmの位置に存在するF及びSiの総量が0.3atm%未満であるクリーニングブレードを備える画像形成装置に比べて、クリーニングブレードの接触部での摩耗が経時においても抑制される画像形成装置が提供される。 <10>に係る発明によれば、転写対向ベルトに接触する表層にシリコーン系ポリマーを含まず、フッ素系化合物を含むクリーニングブレードを備える画像形成装置に比べて、クリーニングブレードの接触部での摩耗が抑制される画像形成装置が提供される。 <11>に係る発明によれば、クリーニングブレードが転写対向ベルトに対して1.5gf/mm未満の押し付け圧で接触する画像形成装置に比べて、転写対向ベルトとクリーニングブレードとの接触箇所でのトナーのすり抜けの発生が抑制される画像形成装置が提供され、クリーニングブレードが転写対向ベルトに対して3.5gf/mm超の押し付け圧で接触する画像形成装置に比べて、転写対向ベルトの表面におけるトナーフィルミングの発生がより抑制される画像形成装置が提供される。 <12>に係る発明によれば、転写対向ベルトが、カーボンブラックを含有しない導電性弾性層を有する画像形成装置に比べて、転写対向ベルトとクリーニングブレードとの接触箇所でのトナーのすり抜けの発生が抑制される画像形成装置が提供される。 <13>に係る発明によれば、転写対向ベルトに接触する表面での押し込み弾性率が35MPa超であるクリーニングブレード、又は転写対向ベルトに接触する表面から200nm以内に存在するF及びSiの総量が、表面から5μm以内に存在するF及びSiの総量に対し75%未満であるクリーニングブレードを用いたクリーニング工程を有する画像形成方法に比べて、転写対向ベルト表面上でのトナーフィルミングの発生が抑制され、かつクリーニングブレードにおける摩耗が抑制された画像形成方法が提供される。
Smart Images

Figure 2025023759000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an image forming apparatus and an image forming method. [Background technology]
[0002] In electrophotographic image forming apparatuses (copiers, facsimiles, printers, etc.), a toner image formed on the surface of an image carrier is transferred to the surface of a recording medium and fixed on the recording medium to form an image. In order to improve the transferability when transferring the toner image to the recording medium, some image forming apparatuses are provided with a transfer belt that contacts the surface of the recording medium opposite to the surface onto which the toner image is transferred. A cleaning blade is used to clean the outer peripheral surface of the transfer belt.
[0003] For example, Patent Document 3 discloses "a cleaning blade formed by cutting a plate-shaped body made of a cured polyurethane resin composition, in which an end face of the cleaning blade formed by the above cutting has 4 atom % or more of silicon atoms (Si) present due to the adhesion of an organosiloxane and an oxygenation treatment." [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-051565 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present disclosure has an objective of providing an image forming apparatus and an image forming method in which the occurrence of toner filming on the surface of a transfer opposing belt is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus and an image forming method equipped with a cleaning blade in which the indentation elasticity modulus on the surface in contact with the transfer opposing belt exceeds 35, or in which the total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Means for solving the problem]
[0006] Means for solving the above problems include the following aspects. <1> An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; a transfer means having a transfer facing belt in contact with a surface of a recording medium opposite to a surface onto which the toner image is transferred, and transferring the toner image formed on the surface of the image carrier onto the surface of the recording medium; a cleaning device having a cleaning blade which comes into contact with the outer peripheral surface of the transfer opposing belt to clean the outer peripheral surface, the cleaning blade being made of polyurethane resin, the indentation elasticity of the surface which comes into contact with the transfer opposing belt being 15 MPa or more and 35 MPa or less, and the total amount of F and Si present within 200 nm from the surface which comes into contact with the transfer opposing belt being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising: <2> the amount of the release agent present within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle; <1> 2. The image forming apparatus according to claim 1 . <3> The melting temperature of the release agent is 70° C. or higher and 75° C. or lower. <1> or <2> 2. The image forming apparatus according to claim 1 . <4> The cleaning blade has an indentation elastic modulus of 20 MPa or more and 30 MPa or less. <1> ~ <3> 13. The image forming apparatus according to claim 12, <5> the cleaning blade has a surface that comes into contact with the transfer belt, and the total amount of F and Si present within 200 nm of the surface accounts for 85% or more of the total amount of F and Si present within 5 μm of the surface; <1> ~ <4> 13. The image forming apparatus according to claim 12, <6> the cleaning blade has a surface that comes into contact with the transfer belt and has a total amount of F and Si of 15 atm % or more; <1> ~ <5> 13. The image forming apparatus according to claim 12, <7> the cleaning blade has a surface that comes into contact with the transfer belt having a total amount of F and Si of 18 atm % or more and 25 atm % or less; <6> 2. The image forming apparatus according to claim 1 . <8> the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the transfer opposing belt of 0.3 atm % or more; <1> ~ <7> 13. The image forming apparatus according to claim 12, <9> the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the transfer opposing belt of 0.3 atm % or more and 2.0 atm % or less; <8> 2. The image forming apparatus according to claim 1 . <10> the cleaning blade contains a silicone-based polymer in a surface layer that contacts the transfer belt; <1> ~ <9> 13. The image forming apparatus according to claim 12, <11> the cleaning blade is brought into contact with the transfer belt at a pressing pressure of 1.5 gf / mm or more and 3.5 gf / mm or less; <1> ~ <10> 13. The image forming apparatus according to claim 12, <12> The transfer belt has a conductive elastic layer containing carbon black and a surface layer containing 35% by mass or more of polytetrafluoroethylene particles. <1> ~ <11> 13. The image forming apparatus according to claim 12, <13> a charging step of charging a surface of an image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of transferring the toner image formed on the surface of the image carrier onto the surface of the recording medium by contacting a transfer opposing belt with a surface of the recording medium opposite to the surface onto which the toner image is transferred; a cleaning step of contacting an outer peripheral surface of the transfer opposing belt with a cleaning blade made of polyurethane resin, having an indentation elastic modulus of 15 to 35 at a surface in contact with the transfer opposing belt, and having a total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing belt that accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising: Effect of the Invention
[0007] <1> According to the invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade whose surface in contact with the transfer opposing belt has an indentation elastic modulus of more than 35 MPa, or a cleaning blade in which the total amount of F and Si present within 200 nm of the surface in contact with the transfer opposing belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. <2> According to the present invention, an image forming apparatus is provided that has excellent low-temperature fixing ability of images compared to an image forming apparatus in which the release agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle. <3> According to the invention, an image forming apparatus is provided which is superior in low-temperature image fixing ability compared to an image forming apparatus in which the melting temperature of the release agent is higher than 75°C, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed compared to an image forming apparatus in which the melting temperature of the release agent is lower than 70°C. <4> According to the invention, an image forming apparatus is provided in which the occurrence of toner slip-through at the contact point between the transfer opposing belt and the cleaning blade is suppressed compared to an image forming apparatus in which the indentation elasticity modulus of the cleaning blade is less than 20 MPa, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed compared to an image forming apparatus in which the indentation elasticity modulus of the cleaning blade is more than 30 MPa. <5> According to the invention, there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface that contacts the transfer opposing belt is less than 85% of the total amount of F and Si present within 5 μm from the surface. <6> or <7> According to the present invention, there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present on the surface that contacts the transfer belt is less than 15 atm %. <8> or <9> According to the present invention, there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed over time, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface that contacts the transfer opposing belt is less than 0.3 atm %. <10> According to the present invention, there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed compared to an image forming apparatus having a cleaning blade that does not contain a silicone-based polymer in the surface layer that contacts the transfer opposing belt and that contains a fluorine-based compound. <11> According to the invention, an image forming apparatus is provided in which the occurrence of toner slip-through at the contact point between the transfer opposing belt and the cleaning blade is suppressed compared to an image forming apparatus in which the cleaning blade contacts the transfer opposing belt with a pressing pressure of less than 1.5 gf / mm, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is further suppressed compared to an image forming apparatus in which the cleaning blade contacts the transfer opposing belt with a pressing pressure of more than 3.5 gf / mm. <12> According to the invention, an image forming apparatus is provided in which the occurrence of toner slip-through at the contact point between the transfer opposing belt and the cleaning blade is suppressed compared to an image forming apparatus in which the transfer opposing belt has a conductive elastic layer that does not contain carbon black. <13> According to the invention, an image forming method is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed and wear in the cleaning blade is suppressed, compared to an image forming method having a cleaning step using a cleaning blade whose surface in contact with the transfer opposing belt has an indentation elasticity modulus of more than 35 MPa, or a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a schematic diagram illustrating an example of a transfer opposing belt used in the present embodiment. [Diagram 2] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 3] 5A and 5B are schematic diagrams for explaining the pressing pressure of a cleaning blade against a transfer opposing belt. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the present embodiment, which is an example of the present disclosure, will be described. These descriptions and examples are merely illustrative of the embodiment, and do not limit the scope of the embodiment.
[0010] In the numerical ranges described in the present embodiment, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range described in the present embodiment. In addition, in the numerical ranges described in the present embodiment, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In this embodiment, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. When the embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this. In this embodiment, each component may contain multiple types of corresponding substances. When referring to the amount of each component in the composition in this embodiment, if multiple substances corresponding to each component are present in the composition, the amount refers to the total amount of the multiple substances present in the composition, unless otherwise specified.
[0011] [Image forming equipment] The image forming apparatus according to this embodiment includes an image holder, a charging means for charging the surface of the image holder, an electrostatic image forming means for forming an electrostatic image on the charged surface of the image holder, a developing means for accommodating an electrostatic image developer containing a toner having toner particles and for developing the electrostatic image formed on the surface of the image holder by the electrostatic image developer as a toner image, a transfer means having a transfer opposing belt in contact with the surface of the recording medium opposite to the surface to which the toner image is transferred (hereinafter simply referred to as the "rear surface") and for transferring the toner image formed on the surface of the image holder to the surface of the recording medium, and a cleaning device having a cleaning blade for contacting and cleaning the outer peripheral surface of the transfer opposing belt. The toner particles have a releasing agent present in a region within 800 nm from the surface that accounts for 70% or more of the releasing agent in the entire toner particle, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less. The cleaning blade is made of a polyurethane resin, and has an indentation elastic modulus of 15 MPa to 35 MPa at the surface in contact with the transfer belt. The total amount of F and Si present within 200 nm from the surface in contact with the transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0012] The image forming apparatus according to the present embodiment, with the above-described configuration, suppresses the occurrence of toner filming on the surface of the transfer belt and suppresses wear on the cleaning blade. The reasons for this are presumed to be as follows.
[0013] In the transfer section of an image forming apparatus where a toner image is transferred to a recording medium, vibrations often occur due to the influence of the passage of the recording medium, etc. In a case where a cleaning device that brings a cleaning blade into contact with the outer peripheral surface of a transfer opposed belt for cleaning is further provided in addition to a transfer means having a transfer opposed belt that contacts the back surface of the recording medium, the load on the cleaning blade increases momentarily due to the influence of the vibrations, and the cleaning blade is not pressed against the transfer opposed belt stably, resulting in unstable cleaning performance. Therefore, in order to increase the robustness against vibration (i.e., the property of being less susceptible to external factors such as vibration) in the cleaning device for the transfer opposing belt, a method of providing a load adjustment mechanism for the cleaning blade can be considered. That is, a method of controlling the load applied from the cleaning blade to the transfer opposing belt by the load adjustment mechanism to keep the cleaning blade pressed against the transfer opposing belt with a stable pressure and stabilize the cleaning performance can be considered. However, providing a load adjustment mechanism complicates the control mechanism in the image forming apparatus, which is a factor in increasing costs. Therefore, there is a demand for realizing stable cleaning performance for the transfer opposing belt without providing a load adjustment mechanism.
[0014] Also, from the viewpoint of suppressing energy consumption, a toner image with excellent low-temperature fixability is desired. Therefore, from the viewpoint of improving the low-temperature fixability of an image, a toner having toner particles with low-melting-temperature wax unevenly distributed on the surface layer, specifically, a toner in which the release agent present in the region within 800 nm from the surface of the toner particles is 70% or more of the release agent of the entire toner particle, and the melting temperature of the release agent is 65°C or more and 80°C or less, has been considered. However, when toner particles with low-melting-temperature wax unevenly distributed on the surface layer are used, toner filming may easily occur on the surface of the transfer opposing belt. This is considered to be because the toner particles with low-melting-temperature wax unevenly distributed on the surface layer as described above tend to have a soft surface and are easily crushed by the pressure from the cleaning blade. From the above viewpoints, in an image forming apparatus using toner particles having the above-mentioned low melting temperature wax unevenly distributed on the surface thereof and having a cleaning device that cleans the surface of a transfer opposing belt with a cleaning blade, it is desired to suppress the occurrence of toner filming on the surface of a transfer opposing belt without providing a load adjustment mechanism in the cleaning device.
[0015] It is possible to suppress toner filming by increasing the pressing pressure of the cleaning blade pressed against the transfer belt to improve scraping performance. However, when the pressing pressure is increased, the cleaning blade becomes worn out and the life of the cleaning blade becomes shorter. Therefore, in addition to suppressing toner filming, it is also required to suppress the wear of the cleaning blade.
[0016] In contrast, the image forming apparatus according to the present embodiment uses a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the transfer belt is 75% or more of the total amount of F and Si present within 5 μm from the surface. In other words, F and Si are unevenly distributed in the cleaning blade near the contact portion with the transfer belt. The presence of at least one of F and Si in the contact portion reduces the friction of the cleaning blade, suppressing wear of the cleaning blade. In addition, even if the load on the cleaning blade increases momentarily due to vibration, the behavior of the tip of the contact portion is stabilized because the friction of the cleaning blade is reduced. As a result, stable cleaning performance is exhibited. In addition, in this embodiment, a cleaning blade having a pressing elastic modulus of 35 MPa or less on the surface that contacts the transfer belt is used, that is, the surface pressure applied from the cleaning blade to the transfer belt is reduced, so that the occurrence of toner filming on the surface of the transfer belt is suppressed even if toner particles having low melting temperature wax unevenly distributed on the surface layer as described above are used.
[0017] From the above, it is presumed that the image forming apparatus according to this embodiment suppresses the occurrence of toner filming on the surface of the transfer opposing belt, and also suppresses wear on the cleaning blade.
[0018] (toner) The toner contained in the electrostatic image developer used in the image forming apparatus according to this embodiment will be described. The toner contains toner particles, and the release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particle, and the melting temperature of the release agent is 65°C or more and 80°C or less.
[0019] The toner particles contain a release agent, and may further contain a binder resin. The toner particles may also contain other internal additives such as a colorant.
[0020] -Release agent- The melting temperature of the release agent is 65° C. to 80° C., preferably 68° C. to 77° C., and more preferably 70° C. to 75° C. When the melting temperature of the release agent is 80° C. or less, the low-temperature fixing property of the image can be improved. On the other hand, when the melting temperature of the release agent is 65° C. or more, the occurrence of toner filming on the transfer belt surface can be suppressed.
[0021] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining the melting temperature in JIS K-7121-1987 "Method for measuring transition temperature of plastics."
[0022] More than 70% of the total release agent is present within 800 nm from the surface of the toner particles (hereinafter, the proportion of the release agent present within 800 nm from the surface of the toner particles is also referred to as the "surface proportion of the release agent"). The surface layer ratio of the release agent is 70% or more, preferably 75% or more, and more preferably 80% or more. The upper limit of the surface layer ratio of the release agent is preferably 100%. By making the surface layer ratio of the release agent 70% or more, the low temperature fixability of the image can be improved.
[0023] Here, a method for measuring the surface layer proportion of the release agent will be described. Samples and images for measurement are prepared in the following manner. The toner is mixed and embedded in an epoxy resin, and the epoxy resin is solidified. The solidified product is cut by an ultramicrotome device (UltracutUCT manufactured by Leica) to prepare a thin specimen having a thickness of 80 nm to 130 nm. Then, an SEM image of the thin specimen is obtained by an ultra-high resolution field emission scanning electron microscope (FE-SEM, S-4800 manufactured by Hitachi High-Technologies Corporation). In the SEM image, a cross section of a toner particle whose maximum length is 85% or more of the volume average particle diameter of the toner particle is selected, the domain of the release agent is observed, the area of the release agent of the entire toner particle and the area of the release agent present in the region within 800 nm from the surface of the toner particle are obtained, and the ratio of the two areas (area of the release agent present in the region within 800 nm from the surface of the toner particle / area of the release agent of the entire toner particle) is calculated. Then, this calculation is performed for 100 toner particles, and the average value is taken as the surface layer ratio of the release agent. The reason for selecting a toner particle cross section whose maximum length is 85% or more of the volume average particle diameter of the toner particle is that a cross section that is less than 85% of the volume average particle diameter is expected to be a cross section of the end of a toner particle, and the cross section of the end of a toner particle does not well reflect the state of the domains in the toner particle.
[0024] As a method for controlling the surface layer ratio of the release agent to 70% or more, for example, there is a method in which the toner particles have a core-shell structure and the release agent is used when forming the shell.
[0025] Examples of the release agent include hydrocarbon waxes such as paraffin wax, natural waxes such as carnauba wax, rice wax, candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, ester waxes such as fatty acid esters and montan acid esters, etc. The release agent is not limited to these. As the release agent, for example, a hydrocarbon wax is preferably used. The hydrocarbon wax is a wax having a hydrocarbon skeleton, and examples thereof include Fischer-Tropsch wax, polyethylene wax (wax having a polyethylene skeleton), polypropylene wax (wax having a polypropylene skeleton), paraffin wax (wax having a paraffin skeleton), and microcrystalline wax. Among these, from the viewpoint of fixability, the hydrocarbon wax is preferably Fischer-Tropsch wax, polyethylene wax, or polypropylene wax. In addition, from the viewpoint of fixability, it is preferable that a plurality of kinds of hydrocarbon waxes are contained in the toner particles. The proportion of the hydrocarbon wax in the total release agent is 85% by mass or more, preferably 95% by mass or more, and more preferably 100% by mass.
[0026] The content of the release agent is, for example, preferably from 1% by mass to 20% by mass, more preferably from 3% by mass to 20% by mass, even more preferably from 3% by mass to 15% by mass, and even more preferably from 5% by mass to 15% by mass, based on the total amount of the toner particles.
[0027] -Binding resin- As the binder resin, for example, a polyester resin is preferably used. The ratio of the polyester resin to the total binder resin is, for example, 75% by mass or more, preferably 90% by mass or more, and more preferably 100% by mass.
[0028] The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.
[0029] The "crystalline" nature of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, the half-width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.
[0030] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. The amorphous polyester resin may be a commercially available product or a synthesized product.
[0031] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0032] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0033] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."
[0034] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.
[0035] The amorphous polyester resin can be obtained by a known manufacturing method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.
[0036] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. The crystalline polyester resin may be a commercially available product or a synthesized product. Here, the crystalline polyester resin is preferably a polycondensate using a polymerizable monomer having a linear aliphatic group rather than a polymerizable monomer having an aromatic group, since the crystalline polyester resin can easily form a crystalline structure.
[0037] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0038] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0039] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.
[0040] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."
[0041] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0042] The crystalline polyester resin can be obtained by a known manufacturing method, for example, in the same manner as the amorphous polyester.
[0043] Here, the binder resin may be used in combination with the polyester resin, and preferably includes a styrene (meth)acrylic resin.
[0044] -Styrene (meth)acrylic resin- Styrene (meth)acrylic resin is a copolymer obtained by copolymerizing at least a monomer having a styrene skeleton and a monomer having a (meth)acryloyl group. "(meth)acrylic acid" is an expression that includes both "acrylic acid" and "methacrylic acid". Also, "(meth)acryloyl group" is an expression that includes both "acryloyl group" and "methacryloyl group".
[0045] Examples of monomers having a styrene skeleton (hereinafter referred to as "styrene-based monomers") include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more. Of these, as the styrene-based monomer, styrene is preferred from the viewpoints of ease of reaction, ease of reaction control, and availability.
[0046] Examples of monomers having a (meth)acryloyl group (hereinafter referred to as "(meth)acrylic monomers") include (meth)acrylic acid and (meth)acrylic acid esters. Examples of the (meth)acrylic acid ester include (meth)acrylic acid alkyl esters (e.g., n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, amyl (meth)acrylate, Examples of the (meth)acrylate include neopentyl acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate esters (for example, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, t-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, and (meth)acrylamide. The (meth)acrylic acid monomers may be used alone or in combination of two or more.
[0047] The copolymerization ratio of the styrene monomer to the (meth)acrylic monomer (mass basis, styrene monomer / (meth)acrylic monomer) may be, for example, 85 / 15 to 70 / 30.
[0048] The styrene (meth)acrylic resin preferably has a crosslinked structure in terms of suppressing image offset. Examples of the styrene (meth)acrylic resin having a crosslinked structure include a crosslinked product obtained by copolymerizing at least a monomer having a styrene skeleton, a monomer having a (meth)acrylic acid skeleton, and a crosslinkable monomer.
[0049] The crosslinkable monomer may, for example, be a bifunctional or higher functional crosslinking agent. Examples of bifunctional crosslinking agents include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylene bis(meth)acrylamide, decanediol diacrylate, glycidyl (meth)acrylate, etc.), polyester type di(meth)acrylate, 2-([1'-methylpropylideneamino]carboxyamino)ethyl methacrylate, etc. Examples of polyfunctional crosslinking agents include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., tetramethylolmethane tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl asocyanurate, triallyl isocyanurate, triallyl trimellitate, diaryl chlorendate, etc.
[0050] The copolymerization ratio of the crosslinkable monomer to the total monomers (mass basis, crosslinkable monomer / total monomers) may be, for example, 2 / 1000 to 30 / 1000.
[0051] The weight average molecular weight of the styrene (meth)acrylic resin is, for example, from 30,000 to 200,000, preferably from 40,000 to 100,000, and more preferably from 50,000 to 80,000, in terms of suppressing image offset. The weight average molecular weight of the styrene (meth)acrylic resin is a value measured by the same method as that for the weight average molecular weight of the polyester resin.
[0052] The content of the styrene (meth)acrylic resin is, for example, from 10% by mass to 30% by mass, preferably from 12% by mass to 28% by mass, and more preferably from 15% by mass to 25% by mass, in terms of achieving both the fluidity and storage stability of the toner and the suppression of image offset, relative to the toner particles.
[0053] Furthermore, other binder resins may be used in combination as the binder resin. Other binder resins include, for example, vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers made of a combination of two or more of these monomers. Examples of other binder resins include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the presence of these. These other binder resins may be used alone or in combination of two or more kinds.
[0054] The content of the binder resin is, for example, preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total amount of the toner particles.
[0055] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, and tetrahydrofuran. Examples of the dyes include various pigments such as phosphorus blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.
[0056] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.
[0057] The content of the colorant is, for example, preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.
[0058] -Other additives- Examples of other additives in the toner include well-known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.
[0059] -Characteristics of toner particles- The toner particles may be toner particles of a single layer structure, or may be toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) that coats the core, and the core-shell structure is preferable. The toner particles of the core-shell structure are preferably composed of, for example, a core composed of a binder resin and a colorant, and a coating layer composed of a binder resin and a release agent.
[0060] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0061] Various average particle sizes and various particle size distribution indexes of the toner particles are measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each divided particle size range (channel) from the smallest diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the volume average particle size D50v, the number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and the number particle size D84p. Using these, the volume average particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number average particle size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as:
[0062] The shape factor SF1 of the toner particles is preferably 110 or more and 150 or less, and more preferably 120 or more and 140 or less.
[0063] The shape factor SF1 is calculated by the following formula. Formula: SF1=(ML 2 / A)×(π / 4)×100 In the above formula, ML represents the absolute maximum length of the toner, and A represents the projected area of the toner. Specifically, the shape factor SF1 is quantified mainly by analyzing a microscope image or a scanning electron microscope image using an image analyzer, and is calculated as follows: That is, an optical microscope image of particles scattered on the surface of a slide glass is captured by a video camera into a Luzex image analyzer, the maximum length and projected area of 100 particles are determined, and the above formula is used to calculate the average value.
[0064] -External additives- The toner may further contain an external additive in addition to the toner particles. Examples of the external additive include inorganic particles, such as SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2)n, Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, and MgSO4.
[0065] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobic treatment agent is, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.
[0066] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles).
[0067] The amount of the external additive added is, for example, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.
[0068] -Toner manufacturing method- The toner used in the image forming apparatus according to the present embodiment is produced by producing toner particles, and then, when an external additive is contained, externally adding the external additive to the toner particles.
[0069] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and well-known production methods are used. Among them, it is preferable to obtain the toner particles by the aggregation and coalescence method.
[0070] Each step of the aggregation and coalescence method will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant will be described, but the colorant is used as necessary. Of course, additives other than the colorant may be used.
[0071] ·Resin particle dispersion preparation process First, a resin particle dispersion liquid in which polyester resin particles serving as a binder resin are dispersed, a colorant dispersion liquid in which colorant particles are dispersed, and a release agent particle dispersion liquid in which release agent particles are dispersed are prepared.
[0072] The polyester resin particle dispersion liquid is prepared, for example, by dispersing polyester resin particles in a dispersion medium with the aid of a surfactant.
[0073] The dispersion medium used in the polyester resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water; alcohols; etc. These may be used alone or in combination of two or more.
[0074] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.
[0075] Examples of methods for dispersing polyester resin particles in a dispersion medium include general dispersion methods using a rotary shear homogenizer, a ball mill with media, a sand mill, a dyno mill, etc. Alternatively, polyester resin particles may be dispersed in a dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then water (W phase) is added to invert the phase from W / O to O / W, dispersing the resin in particulate form in an aqueous medium.
[0076] The volume average particle size of the polyester resin particles dispersed in the polyester resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle diameter of the polyester resin particles is determined by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), drawing a cumulative distribution for the volume of the divided particle size range (channel) from the small particle size side, and determining the particle size that accounts for 50% by volume of all particles as the volume average particle diameter D50v. The volume average particle diameters of particles in other dispersions are also measured in the same manner.
[0077] The content of the polyester resin particles contained in the polyester resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.
[0078] The colorant dispersion and the release agent particle dispersion are also prepared in the same manner as the polyester resin particle dispersion. That is, the dispersion medium, the dispersion method, the volume average particle size of the particles, and the content of the particles in the polyester resin particle dispersion are the same for the colorant dispersion and the release agent particle dispersion.
[0079] ·First agglomerated particle formation step Next, the polyester resin particle dispersion and the colorant dispersion are mixed. Then, in the mixed dispersion, the polyester resin particles and the colorant particles are hetero-aggregated to form first aggregate particles containing the polyester resin particles and the colorant particles and having a diameter close to that of the target toner particles. If necessary, a release agent particle dispersion may also be mixed to cause the first aggregate particles to contain the release agent particles.
[0080] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the polyester resin (specifically, for example, −30° C. or more and −10° C. or less of the glass transition temperature of the polyester resin), and the particles dispersed in the mixed dispersion are aggregated to form first aggregated particles. In the first aggregate particle formation step, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.
[0081] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the flocculant used is reduced, and the charging characteristics are improved. An additive that forms a complex or a similar bond with the metal ions of the flocculant may be used together with the flocculant, and a chelating agent is preferably used as this additive.
[0082] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0083] ·Second agglomerated particle formation process After obtaining the first aggregated particle dispersion in which the first aggregated particles are dispersed, the first aggregated particle dispersion, the polyester resin particle dispersion, and the release agent particle dispersion are further mixed. The polyester resin particle dispersion and the release agent particle dispersion may be mixed in advance, and the mixture may be mixed into the first aggregated particle dispersion.
[0084] Then, in the mixed dispersion liquid in which the first aggregated particles, polyester resin particles, and release agent particles are dispersed, the polyester resin particles and release agent particles are aggregated so as to adhere to the surfaces of the first aggregated particles, thereby forming second aggregated particles.
[0085] Specifically, for example, in the first aggregate particle forming step, when the first aggregate particles reach a target particle size, a dispersion in which polyester resin particles and release agent particles are dispersed is mixed into the first aggregate particle dispersion, and then the mixed dispersion is heated at a temperature equal to or lower than the glass transition temperature of the polyester resin, and the pH of the mixed dispersion is adjusted to, for example, a range of about 6.5 to 8.5 to stop the progress of aggregation.
[0086] As a result, second aggregated particles are obtained, which are aggregated such that the polyester resin particles and the release agent particles adhere to the surfaces of the first aggregated particles.
[0087] ·Fusion / coalescence process Next, the second aggregate particle dispersion liquid in which the second aggregate particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the polyester resin (for example, a temperature 10° C. to 50° C. higher than the glass transition temperature of the polyester resin) to fuse and coalesce the second aggregate particles, thereby forming toner particles.
[0088] Through the above steps, toner particles are obtained. Note that the toner particles may be produced through a process in which, after obtaining the second aggregated particle dispersion in which the second aggregated particles are dispersed, the second aggregated particle dispersion is further mixed with a polyester resin particle dispersion in which polyester resin particles are dispersed, and the polyester resin particles are aggregated so that the polyester resin particles are further attached to the surfaces of the second aggregated particles, thereby forming third aggregated particles, and a process in which the third aggregated particle dispersion in which the third aggregated particles are dispersed is heated to fuse and coalesce the third aggregated particles, thereby forming toner particles.
[0089] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dry toner particles. In the washing step, from the viewpoint of electrostatic chargeability, it is preferable to carry out sufficient replacement washing with ion-exchanged water. In addition, the solid-liquid separation step is not particularly limited, but from the viewpoint of productivity, it is preferable to carry out suction filtration, pressure filtration, etc. In addition, in the drying step, there is no particular limit to the method, but from the viewpoint of productivity, it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.
[0090] The toner according to the present embodiment is produced, for example, by adding an external additive to dry toner particles and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.
[0091] -Electrostatic image developer- In this embodiment, the electrostatic image developer contained in the developing unit contains at least the above-mentioned toner. The electrostatic image developer may be a one-component developer containing only the toner, or may be a two-component developer in which the toner is mixed with a carrier.
[0092] The carrier is not particularly limited, and may be a known carrier. For example, the carrier may be a coated carrier in which the surface of a core material made of magnetic powder is coated with a resin; a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin; etc. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material, and the surface of the carrier is coated with a resin.
[0093] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.
[0094] Examples of the conductive particles include metals such as gold, silver, and copper; and particles of carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0095] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing organosiloxane bonds or modified products thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The coating resin and matrix resin may contain additives such as conductive materials.
[0096] To coat the surface of the core material with a resin, a method of coating with a coating layer forming solution in which the coating resin and various additives (used as necessary) are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited, and may be selected taking into consideration the type of resin used, coating suitability, etc. Specific resin coating methods include an immersion method in which the core material is immersed in the coating layer forming solution; a spray method in which the coating layer forming solution is sprayed on the core material surface; a fluidized bed method in which the coating layer forming solution is sprayed on the core material while it is suspended in flowing air; and a kneader coater method in which the carrier core material and the coating layer forming solution are mixed in a kneader coater and then the solvent is removed; and the like.
[0097] The mixture ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.
[0098] (cleaning blade) The cleaning blade used in the image forming apparatus according to this embodiment will be described. The cleaning blade is made of polyurethane resin. The indentation elasticity of the surface (contact portion) of the cleaning blade that contacts the transfer belt is 15 MPa or more and 35 MPa or less. In addition, the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade that contacts the transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0099] The cleaning blade may be a single-layer blade consisting of one layer, a two-layer blade consisting of an edge layer (a layer that contacts the transfer belt) and a back layer, or a laminated configuration of three or more layers.
[0100] -Indentation elastic modulus- The cleaning blade has an indentation elastic modulus of 15 MPa or more and 35 MPa or less at the surface (contact portion) that contacts the transfer opposing belt. With an indentation elastic modulus of 15 MPa or more, the occurrence of toner slipping through at the contact portion between the transfer opposing belt and the cleaning blade is suppressed. With an indentation elastic modulus of 35 MPa or less, the occurrence of toner filming on the transfer opposing belt and the surface of the transfer opposing belt is suppressed. The indentation elastic modulus is more preferably 20 MPa or more and 30 MPa or less, and more preferably 22 MPa or more and 28 MPa or less.
[0101] The indentation modulus is measured based on the slope of the unloading curve obtained during unloading from the load-penetration curve of the indenter in the load range of 65% to 95% of the maximum load in accordance with ISO14577 (2002). The measurement conditions are as follows: Measuring device: Nanoindentation method Dynamic ultra-microhardness tester "Product name PICODENTOR HM500 (manufacturer Fisher Instruments)" Indenter: Berkovich-type conical diamond indenter with a face angle of 120° Indenter depth: 20μm Indenter pressing speed: 12.5μm / sec Indenter unloading speed: 12.5m / sec The above measurements are carried out on the surface (contact portion) of the cleaning blade that comes into contact with the transfer belt.
[0102] - Surface layer ratio of F and Si - The cleaning blade has a ratio (surface layer ratio of F and Si) of the total amount of F and Si present within 200 nm from the surface (contact portion) that contacts the transfer belt to the total amount of F and Si present within 5 μm from the surface of the cleaning blade is 75% or more. When the surface layer ratio of F and Si at the contact portion of the cleaning blade is 75% or more, the friction of the contact portion of the cleaning blade is reduced and the occurrence of wear is suppressed. The surface layer ratio of F and Si at the contact portion of the cleaning blade is more preferably 85% or more, and more preferably 90% or more. On the other hand, the upper limit of the surface layer ratio of F and Si at the contact portion of the cleaning blade is not particularly limited, but is preferably 95% or less, more preferably 93% or less. When the surface layer ratio of F and Si at the contact portion of the cleaning blade is 95% or less, the occurrence of belly contact (reduction in surface pressure) due to insufficient tack formation at the contact portion of the cleaning blade is suppressed.
[0103] - Surface F and Si content - The cleaning blade has a total amount of F and Si (surface F and Si amount) present on the surface (contact portion) that contacts the transfer belt of preferably 15 atm% or more, more preferably 18 atm% or more, and even more preferably 20 atm% or more. By having the surface F and Si amount at the contact portion of the cleaning blade of 15 atm% or more, the friction of the contact portion of the cleaning blade is reduced, and the occurrence of wear is suppressed. The upper limit of the surface F and Si content at the contact portion of the cleaning blade is not particularly limited, but from the viewpoint of suppressing the occurrence of chipping at the contact portion of the cleaning blade, it is preferably 25 atm % or less, and more preferably 22 atm % or less.
[0104] -50nm position F and Si amount- The cleaning blade has a total amount of F and Si (amount of F and Si at 50 nm) of 0.3 atm% or more at a position 50 nm from the surface (contact portion) that contacts the transfer belt, more preferably 0.5 atm% or more, and even more preferably 1.0 atm% or more. By having the amount of F and Si at 50 nm of the cleaning blade of 0.3 atm% or more, low friction at the contact portion of the cleaning blade is maintained, and wear is suppressed over time. The upper limit values of the 50 nm position F and the Si content of the cleaning blade are not particularly limited, but from the viewpoint of suppressing the occurrence of chipping at the contact portion of the cleaning blade over time, they are preferably 7.0 atm% or less, more preferably 5.0 atm% or less, and even more preferably 2.0 atm% or less.
[0105] A method for measuring the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of a cleaning blade that contacts a transfer belt to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) will be described. That is, a method for analyzing the amount of F element and the amount of Si element in the depth direction from the contact portion of the cleaning blade will be described. An area including the surface (contact portion) of the cleaning blade that comes into contact with the transfer belt is cut out, and the amount (atm%) of each of the elements N, C, O, F, and Si is measured in the depth direction from the contact portion using XPS (Versa Probe II manufactured by Ulvac-PHI).
[0106] The total amount of F and Si present on the surface (contact portion) of the cleaning blade that comes into contact with the transfer belt is determined by plotting the depth from the contact portion of the cleaning blade obtained by the above-mentioned analysis in the depth direction versus element ratio, with the area up to a depth of 5 μm being SA and the area up to a depth of 200 nm being SB, and calculating the ratio from the formula SB / SA × 100. The total amount of F and Si present at a position 50 nm from the surface (contact portion) of the cleaning blade that comes into contact with the transfer belt can be determined in the same manner.
[0107] -composition- The cleaning blade is made of polyurethane resin.
[0108] Polyurethane resin The polyurethane resin is a polyurethane resin obtained by polymerizing at least a polyol component and a polyisocyanate component. If necessary, the polyurethane resin may be a polyurethane resin obtained by polymerizing a resin having a functional group capable of reacting with an isocyanate group of the polyisocyanate in addition to the polyol component.
[0109] The polyurethane resin preferably has a hard segment and a soft segment. The terms "hard segment" and "soft segment" refer to segments in which the material constituting the former is harder than the material constituting the latter, and the material constituting the latter is softer than the material constituting the former, in a polyurethane resin material. Examples of materials constituting the hard segment (hard segment materials) include low molecular weight polyol components among polyol components, resins having functional groups capable of reacting with isocyanate groups of polyisocyanates, etc. On the other hand, examples of materials constituting the soft segment (soft segment materials) include high molecular weight polyol components among polyol components.
[0110] Here, the average particle size of the hard segment aggregates is preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less. By setting the average particle size of the hard segment aggregates to 1 μm or more, the friction resistance on the surface of the contacting member is easily reduced, which stabilizes the blade behavior and makes it easier to suppress local wear. On the other hand, by setting the average particle size of the hard segment aggregates to 10 μm or less, the occurrence of chipping is easily suppressed.
[0111] The average particle size of the hard segment aggregates is measured as follows: Images were taken at a magnification of ×20 using a Pass BX51-P, and the images were binarized through image processing. The particle diameters (circle equivalent diameters) of the aggregates were measured at five points per cleaning blade (the particle diameters of five aggregates were measured at each point) for 20 cleaning blades, and the average particle diameter was calculated from a total of 500 particles. The images were binarized using the image processing software OLYMPUS Stream essentials (Olympus Corporation), and the hue / saturation / brightness thresholds were adjusted so that the crystalline parts and hard segment aggregates were black and the amorphous parts (corresponding to the soft segments) were white.
[0112] Polyol component The polyol component includes a high molecular weight polyol and a low molecular weight polyol.
[0113] The polymer polyol component is a polyol having a number average molecular weight of 500 or more (preferably 500 or more and 5000 or less). Examples of the polymer polyol component include well-known polyols such as polyester polyols obtained by dehydration condensation of low molecular weight polyols and dibasic acids, polycarbonate polyols obtained by reaction of low molecular weight polyols and alkyl carbonates, polycaprolactone polyols, and polyether polyols. Commercially available polymer polyols include, for example, PLACCEL 205 and PLACCEL 240 manufactured by Daicel Corporation.
[0114] Here, the number average molecular weight is a value measured by gel permeation chromatography (GPC). The same applies hereinafter.
[0115] These polymer polyols may be used alone or in combination of two or more kinds.
[0116] The polymerization ratio of the high molecular weight polyol component is preferably 30 mol % or more and 50 mol % or less, and more preferably 40 mol % or more and 50 mol % or less, based on the total polymerization components of the polyurethane resin.
[0117] The low molecular weight polyol component is a polyol having a molecular weight (number average molecular weight) of less than 500. The low molecular weight polyol is a material that functions as a chain extender and a crosslinking agent.
[0118] Examples of the low molecular weight polyol component include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosanediol. Among these, 1,4-butanediol is preferably used as the low molecular weight polyol component.
[0119] Examples of the low molecular weight polyol component include diols (2 functional), triols (3 functional), and tetraols (4 functional), which are well known as chain extenders and crosslinking agents. These polyols may be used alone or in combination of two or more kinds.
[0120] The polymerization ratio of the low molecular weight polyol component is preferably more than 50 mol% and 75 mol% or less, more preferably 52 mol% or more and 75 mol%, more preferably 55 mol% or more and 75 mol% or less, and even more preferably 55 mol% or more and 60 mol% or less, based on the total polymerization components of the polyurethane resin.
[0121] Polyisocyanate component Examples of the polyisocyanate component include 4,4'-diphenylmethane diisocyanate (MDI), 2,6-toluene diisocyanate (TDI), 1,6-hexanediisocyanate (TDI), isocyanate (HDI), 1,5-naphthalene diisocyanate (NDI), and 3,3-dimethylbiphenyl-4,4'-diisocyanate (TODI).
[0122] As the polyisocyanate component, 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), and hexamethylene diisocyanate (HDI) are more preferable.
[0123] These polyisocyanate components may be used alone or in combination of two or more kinds.
[0124] The polymerization ratio of the polyisocyanate component is preferably from 5 mol % to 25 mol %, and more preferably from 10 mol % to 20 mol %, based on the total polymerization components of the polyurethane resin.
[0125] Resins with functional groups that can react with isocyanate groups A resin having a functional group capable of reacting with an isocyanate group (hereinafter referred to as a "functional group-containing resin") is preferably a flexible resin, and from the viewpoint of flexibility, is more preferably an aliphatic resin having a linear structure. Specific examples of functional group-containing resins include acrylic resins containing two or more hydroxyl groups, polybutadiene resins containing two or more hydroxyl groups, and epoxy resins containing two or more epoxy groups.
[0126] An example of a commercially available acrylic resin containing two or more hydroxyl groups is Actflow (grades: UMB-2005B, UMB-2005P, UMB-2005, UME-2005, etc.) manufactured by Soken Chemical & Engineering Co., Ltd.
[0127] An example of a commercially available polybutadiene resin containing two or more hydroxyl groups is R-45HT manufactured by Idemitsu Kosan Co., Ltd.
[0128] The epoxy resin having two or more epoxy groups is not hard and brittle like conventional epoxy resins, but is more flexible and tough than conventional epoxy resins. For example, in terms of molecular structure, the epoxy resin preferably has a structure (flexible skeleton) in its main chain structure that can increase the mobility of the main chain, and examples of the flexible skeleton include an alkylene skeleton, a cycloalkane skeleton, and a polyoxyalkylene skeleton, and the polyoxyalkylene skeleton is particularly preferred. In terms of physical properties, epoxy resins with a lower viscosity relative to the molecular weight are preferred compared to conventional epoxy resins. Specifically, the weight average molecular weight is preferably within the range of 900±100, and the viscosity at 25°C is preferably within the range of 15000±5000 mPa·s, more preferably within the range of 15000±3000 mPa·s. Commercially available epoxy resins with these properties include, for example, EPLICON EXA-4850-150 manufactured by DIC.
[0129] The polymerization ratio of the functional group-containing resin is preferably set within a range that does not impair the properties of the cleaning blade.
[0130] -Method of manufacturing polyurethane resin The polyurethane resin is produced by a general polyurethane production method such as a prepolymer method or a one-shot method. The prepolymer method is suitable for this embodiment because it can produce polyurethane with excellent abrasion resistance and chipping resistance, but the production method is not limited. The cleaning blade is produced by forming the cleaning blade composition prepared by the above-mentioned method into a sheet shape by, for example, centrifugal molding or extrusion molding, and then cutting the sheet into a desired shape.
[0131] Examples of the catalyst used in the production of the polyurethane resin include amine compounds such as tertiary amines, quaternary ammonium salts, and organometallic compounds such as organotin compounds. Examples of the tertiary amine include trialkylamines such as triethylamine, tetraalkyldiamines such as N,N,N',N'-tetramethyl-1,3-butanediamine, aminoalcohols such as dimethylethanolamine, ethoxylated amines, ethoxylated diamines, ester amines such as bis(diethylethanolamine) adipate, triethylenediamine (TEDA), cyclohexylamine derivatives such as N,N-dimethylcyclohexylamine, morpholine derivatives such as N-methylmorpholine and N-(2-hydroxypropyl)-dimethylmorpholine, piperazine derivatives such as N,N'-diethyl-2-methylpiperazine and N,N'-bis-(2-hydroxypropyl)-2-methylpiperazine, and the like.
[0132] Examples of quaternary ammonium salts include 2-hydroxypropyltrimethylammonium octylate, 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) octylate, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) octylate, DBU-oleate, DBU-p-toluenesulfonate, DBU-formate, and 2-hydroxypropyltrimethylammonium formate.
[0133] Examples of the organotin compound include dialkyltin compounds such as dibutyltin dilaurate and dibutyltin di(2-ethylhexoate), stannous 2-ethylcaproate, and stannous oleate.
[0134] Among these catalysts, the tertiary ammonium salt triethylenediamine (TEDA) is used in terms of hydrolysis resistance, and quaternary ammonium salts are preferred in terms of processability. Among the quaternary ammonium salts, 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) octylate, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) octylate, and DBU formate are preferred, as they have high reactivity.
[0135] The content of the catalyst is preferably in the range of 0.0005% by mass to 0.03% by mass, and particularly preferably in the range of 0.001% by mass to 0.01% by mass, of the entire polyurethane resin constituting the contact member. These may be used alone or in combination of two or more.
[0136] - Fabrication of a two-layer cleaning blade For example, when the cleaning blade has a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer are separately produced by the above-mentioned polyurethane resin production method, and the obtained edge layer and back layer are laminated together to produce the cleaning blade. In addition, when the hardness of the edge layer and the back surface layer is to be made different, the material of the polyurethane resin may be changed, for example, by changing the ratio of the hard segment and the soft segment.
[0137] -Contact area modification treatment In this embodiment, in order to set the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade that contacts the transfer belt to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) within the above-mentioned range, it is preferable to have a modified layer that has been subjected to a surface modification treatment by penetrating at least one of F element and Si element into the contact portion of the obtained cleaning blade.
[0138] The modified layer is a layer formed by impregnating the contact portion of the cleaning blade with a surface treatment liquid containing an isocyanate compound, a specific polymer having at least one of an F element and an Si element, and an organic solvent, and then hardening the surface treatment liquid (i.e., the isocyanate compound and the specific polymer). The modified layer is formed integrally with the surface layer of the contact portion so as to become gradually sparser from the surface toward the inside.
[0139] Examples of the isocyanate compound include 2,6-tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), paraphenylene diisocyanate (PPDI), 1,5-naphthalene diisocyanate (NDI), 3,3'-dimethyldiphenyl-4,4'-diisocyanate (TODI), as well as polymers and modified products thereof. Examples of modified products of the isocyanate compound include urethane prepolymers in which an isocyanate compound is prepolymerized together with a polyol.
[0140] The specific polymer is preferably a compound that reacts with an isocyanate compound to form a chemical bond. Examples of acrylic polymers having siloxane bonds include block copolymers of (meth)acrylic acid esters and (meth)acrylic acid siloxane esters, and derivatives thereof. Note that "(meth)acrylic" means either acrylic or methacrylic, or both. Examples of acrylic polymers having fluorine atoms include block copolymers of (meth)acrylic acid esters and fluorinated alkyl (meth)acrylates, and derivatives thereof. The cleaning blade preferably contains a polymer having a siloxane bond (a silicone-based polymer) in the portion that comes into contact with the transfer belt. From the viewpoint of solubility in organic solvents, the specific polymer is preferably a compound having a hydroxyl group, an alkyl group, or a carboxyl group.
[0141] The following methods can be used to confirm that the cleaning blade contains a specific polymer in the surface layer of the contact area, and that the surface layer contains a specific polymer that is an acrylic polymer. Specifically, the confirmation is performed by estimating the structure and analyzing the composition of the surface layer material of the contact area of the cleaning blade using an analytical method such as Fourier transform infrared spectrophotometer (FTIR) or X-ray photoelectron spectroscopy (XPS).
[0142] The content of the specific polymer in the surface treatment liquid is, for example, 8 parts by mass or more and 13 parts by mass or less, preferably 9 parts by mass or more and 13 parts by mass or less, and more preferably 10 parts by mass or more and 13 parts by mass or less, relative to 100 parts by mass of the isocyanate compound.
[0143] The organic solvent is preferably one that dissolves the specific polymer and is compatible with the isocyanate compound, and specific examples thereof include ethyl acetate, methyl ethyl ketone (MEK), toluene, acetone, cyclohexanone, etc. In addition, reactive diluents such as 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, and trimethylolpropane triacrylate may also be used as the organic solvent.
[0144] The modified layer is formed, for example, by impregnating and applying the above-mentioned surface treatment liquid onto at least the contact portion of the cleaning blade, drying to remove the organic solvent, and then heating to form a hardened layer. The impregnation coating method is not particularly limited, and examples thereof include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, curtain coating, etc. When the impregnation coating method is the dip coating method, the immersion time is, for example, in the range of 10 seconds or more and 60 seconds or less. Drying conditions after the impregnation coating include, for example, a temperature of 20° C. to 30° C. and a time of 1 to 10 minutes, and heat treatment conditions include, for example, a temperature of 50° C. to 80° C. and a time of 60 to 90 minutes.
[0145] Pressing pressure The pressing pressure NF (Normal Force) with which the cleaning blade is pressed against the transfer belt is preferably 1.5 gf / mm to 3.5 gf / mm, more preferably 2.3 gf / mm to 3.2 gf / mm. When the pressing pressure NF is 1.5 gf / mm or more, the occurrence of toner slipping through at the contact point between the transfer belt and the cleaning blade is suppressed, and when the pressing pressure NF is 3.5 gf / mm or less, the occurrence of toner filming on the surface of the transfer belt is further suppressed.
[0146] Here, the pressing pressure NF of the cleaning blade is calculated by the following formula. Formula: Pressing pressure NF = k × d In the formula, k is the spring constant specific to the cleaning blade, and d is the amount of penetration of the cleaning blade into the transfer belt (see FIG. 3). The spring constant k specific to the cleaning blade is obtained by applying a displacement to the cleaning blade 12 and measuring the load with a load cell. The amount of penetration d of the cleaning blade into the transfer belt is calculated by fixing the cleaning blade 12 to a supporting member and calculating the amount of displacement of the cleaning blade when the cleaning blade is brought into contact with the transfer belt. In FIG. 3, BE denotes a transfer opposing belt, CB denotes a cleaning blade, and CBS denotes a supporting member for supporting the cleaning blade.
[0147] The amount of penetration d of the cleaning blade into the transfer belt is preferably 0 mm or more and 10 mm or less, and more preferably 0.01 mm or more and 5 mm or less.
[0148] (Transfer opposing belt) In this embodiment, the transfer opposing belt, which is disposed so as to be in contact with the surface of the recording medium opposite to the surface onto which the toner image is transferred, has, for example, a conductive elastic layer (substrate) containing a polymer material and conductive particles, and may further have a surface layer (protective layer) on at least one of the outer peripheral surface and the inner peripheral surface of the substrate.
[0149] Fig. 1 is a schematic perspective view showing an example of a transfer opposing belt. The transfer opposing belt 50 shown in Fig. 1 has a base material (conductive elastic layer) 52, a protective layer (surface layer) 54, and a protective layer (surface layer) 56. The protective layer 54 is provided on the outer peripheral surface of the base material 52, and is a layer that constitutes the outer peripheral surface of the transfer opposing belt 50. The protective layer 56 is provided on the inner peripheral surface of the base material 52, and is a layer that constitutes the inner peripheral surface of the transfer opposing belt 50.
[0150] The layer structure and materials of the transfer opposing belt will be described in detail below.
[0151] [Base material (conductive elastic layer)] The substrate is preferably a film or sheet of a polymeric material containing conductive particles.
[0152] Examples of the polymeric material include rubber and resin. The polymeric material may be used alone or in combination of two or more kinds.
[0153] Examples of rubber include chloroprene rubber, epichlorohydrin rubber, isoprene rubber, butyl rubber, polyurethane, silicone rubber, fluororubber, styrene-butadiene rubber, butadiene rubber, nitrile rubber (NBR), ethylene propylene rubber, ethylene-propylene-diene terpolymer rubber (EPDM), natural rubber, and mixed rubbers thereof.
[0154] Examples of the resin include polyamide, polyimide, polyamideimide, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyethersulfone, polyphenylsulfone, polysulfone, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polycarbonate, polyester, and mixed resins thereof.
[0155] Examples of the conductive particles include carbon black such as ketjen black, oil furnace black, channel black, and acetylene black; metal particles such as aluminum and nickel; and metal oxide particles such as indium tin oxide, tin oxide, zinc oxide, titanium oxide, and yttrium oxide. Carbon black is preferred as the conductive particles. The conductive particles may be used alone or in combination of two or more kinds.
[0156] The average primary particle size of the conductive particles is preferably 1 nm or more and 150 nm or less, more preferably 3 nm or more and 100 nm or less, and even more preferably 5 nm or more and 50 nm or less.
[0157] The substrate may contain a conductive agent other than the conductive particles. Examples of the conductive agent include ion conductive substances such as potassium titanate, potassium chloride, sodium perchlorate, and lithium perchlorate; ion conductive polymers such as polyaniline, polyether, polypyrrole, polysulfone, and polyacetylene; and the like. The conductive agent may be used alone or in combination of two or more.
[0158] The substrate is preferably a conductive elastic layer containing rubber and conductive particles, and more preferably a conductive elastic layer containing at least one of chloroprene rubber and epichlorohydrin rubber, and carbon black.
[0159] The total content of the conductive particles and the conductive agent contained in the substrate is preferably set based on the volume resistivity of the transfer belt. 6 Ω cm or more 1.0×10 9 It is preferable that the resistivity is Ω·cm or less. In this embodiment, the volume resistivity (Ω·cm) is measured as follows. The measurement environment is a temperature of 22°C and a relative humidity of 55%. The sample is placed in the measurement environment for 24 hours or more, and the temperature and humidity are regulated. The resistance measurement device is a microammeter (R8430A manufactured by Advantest Corporation), and the probe is a UR probe (manufactured by Mitsubishi Chemical Corporation). The applied voltage is 1 kV, the application time is 5 seconds, and the load is 1 kgf. The measurement points are 6 points at equal intervals in the circumferential direction of the transfer belt, and 3 points in the center and both ends in the width direction of the transfer belt, for a total of 18 points. The measured values of the 18 points are arithmetically averaged.
[0160] When the substrate contains carbon black, the content of carbon black is preferably 5 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the polymer material.
[0161] The substrate may contain additives such as antioxidants, crosslinking agents, flame retardants, colorants, surfactants, dispersants, and fillers.
[0162] From the viewpoint of the durability of the transfer belt, the average thickness of the substrate is preferably 400 μm or more, more preferably 420 μm or more, and even more preferably 440 μm or more. From the viewpoint of the flexibility and bending resistance of the transfer belt, the average thickness of the substrate is preferably 800 μm or less, more preferably 600 μm or less, and even more preferably 500 μm or less.
[0163] [Protective layer (surface layer)] The transfer belt may have a protective layer on at least one of the outer peripheral surface and the inner peripheral surface of the substrate, and preferably has protective layers on the outer peripheral surface and the inner peripheral surface of the substrate. The protective layer provided on the outer peripheral surface of the substrate constitutes the outer peripheral surface of the transfer belt. The protective layer provided on the inner peripheral surface of the substrate constitutes the inner peripheral surface of the transfer belt.
[0164] The protective layer is preferably a film or sheet containing a polymeric material. Polymeric materials include the rubbers and resins previously described for the substrate.
[0165] The protective layer preferably contains a urethane resin and fluorine-containing resin particles. Urethane resin (also called polyurethane or urethane rubber) is generally synthesized by polymerizing polyisocyanate and polyol. The urethane resin preferably has a hard segment and a soft segment.
[0166] As the fluorine-containing resin particles, for example, one or more of particles made of tetrafluoroethylene resin (polytetrafluoroethylene), trifluorochloroethylene resin, hexafluoropropylene resin, vinyl fluoride resin, vinylidene fluoride resin, difluorodichloroethylene resin, and any of their copolymers are preferable. Among these, as the fluorine-containing resin particles, tetrafluoroethylene resin (polytetrafluoroethylene) particles are preferable.
[0167] The content of the fluorine-containing resin particles in the protective layer is preferably 35% by mass or more, more preferably 38% by mass or more, from the viewpoint of reducing friction at the contact portion with the cleaning blade and suppressing wear of the cleaning blade, while the upper limit of the content of the fluorine-containing resin particles in the protective layer is preferably 50% by mass or less, more preferably 45% by mass or less, from the viewpoint of smoothness of the surface layer. The protective layer preferably contains tetrafluoroethylene resin (polytetrafluoroethylene) particles in an amount of 35% by mass or more, and the upper limit of the content is preferably 50% by mass or less.
[0168] The average primary particle size of the fluorine-containing resin particles is preferably from 5 nm to 300 nm, more preferably from 8 nm to 200 nm, and even more preferably from 10 nm to 150 nm.
[0169] The protective layer may contain additives such as antioxidants, crosslinking agents, flame retardants, colorants, and fillers.
[0170] The average thickness of the protective layer on one side of the substrate is preferably 2 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more from the viewpoint of the abrasion resistance of the protective layer, and is preferably 60 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less from the viewpoint of the flexibility and bending resistance of the transfer opposing belt.
[0171] [Manufacturing method of transfer belt] As a method for producing the transfer opposing belt, for example, a tubular member serving as a base material is prepared, and a protective layer is formed on the outer peripheral surface or inner peripheral surface of the tubular member.
[0172] Methods for manufacturing tubular members include, for example, extrusion molding, in which a composition containing a polymeric material and conductive particles is melted and extruded through a die into a belt-like shape and solidified; injection molding, in which a composition containing a polymeric material and conductive particles is melted and placed in a belt-like mold and solidified; and coating molding, in which a composition containing a precursor or monomer of a polymeric material and conductive particles is applied to a core body and solidified.
[0173] The method for forming the protective layer is, for example, to apply a liquid composition containing a polymeric material and fluorine-containing resin particles to the outer or inner peripheral surface of the tubular member and solidify it; to apply a liquid composition containing a precursor or monomer of the polymeric material and fluorine-containing resin particles to the outer or inner peripheral surface of the tubular member and solidify it; etc. In order to solidify the liquid composition, drying, heating, electron beam irradiation, or ultraviolet ray irradiation may be performed depending on the types of components.
[0174] (Configuration of Image Forming Apparatus) The image forming apparatus according to this embodiment includes an image holder, a charging means for charging the surface of the image holder, an electrostatic image forming means for forming an electrostatic image on the charged surface of the image holder, a developing means for accommodating an electrostatic image developer containing a toner having toner particles and for developing the electrostatic image formed on the surface of the image holder by the electrostatic image developer as a toner image, and a transfer means for transferring the toner image formed on the surface of the image holder to the surface of a recording medium, the transfer means having a transfer opposing belt in contact with the surface (rear surface) of the recording medium opposite to the surface to which the toner image is transferred, and a cleaning device having a cleaning blade for contacting and cleaning the outer peripheral surface of the transfer opposing belt.
[0175] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as an apparatus equipped with a transfer means for transferring a toner image on an image holder onto a recording medium via a secondary transfer body (e.g., a secondary transfer belt); an apparatus equipped with a fixing means for fixing the toner image transferred onto the surface of the recording medium; an apparatus equipped with a cleaning device for cleaning the surface of the image holder before charging after the toner image is transferred; an apparatus equipped with a static elimination device for irradiating the surface of the image holder with static elimination light to eliminate static electricity before charging after the toner image is transferred; and an apparatus equipped with an image holder heating member for increasing the temperature of the image holder and reducing the relative temperature.
[0176] The image forming apparatus according to the present embodiment may be either a dry development type image forming apparatus or a wet development type image forming apparatus (a development type using a liquid developer).
[0177] In the image forming apparatus according to the present embodiment, for example, the portion including the image carrier may be a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a toner image forming device and a transfer device is preferably used.
[0178] (Image forming method) The image forming method according to this embodiment includes a charging step of charging the surface of an image holder, an electrostatic image forming step of forming an electrostatic image on the charged surface of the image holder, a developing step of developing the electrostatic image formed on the surface of the image holder as a toner image using an electrostatic image developer containing a toner having toner particles, a transfer step of transferring the toner image formed on the surface of the image holder to the surface of the recording medium by contacting a transfer opposing belt with the surface of the recording medium opposite to the surface to which the toner image is transferred, and a cleaning step of contacting a cleaning blade with the outer peripheral surface of the transfer opposing belt to clean it. The toner particles have a releasing agent present within 800 nm from the surface that accounts for 70% or more of the releasing agent in the entire toner particle, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less. The cleaning blade is made of polyurethane resin. The cleaning blade has an indentation elastic modulus of 15 to 35 at the surface in contact with the transfer belt. Furthermore, the total amount of F and Si present within 200 nm from the surface in contact with the transfer belt of the cleaning blade accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0179] Hereinafter, an example of an image forming apparatus and an image forming method according to the present embodiment will be described with reference to the drawings. However, the image forming apparatus and the image forming method according to the present embodiment are not limited to this. Note that the main parts shown in the drawings will be described, and the description of the rest will be omitted.
[0180] FIG. 2 is a schematic diagram showing an example of the image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 2 includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming means) of an electrophotographic type that output images of the respective colors of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the image forming apparatus.
[0181] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (an example of an intermediate transfer body) 20 is provided to extend through each unit. The intermediate transfer belt 20 is provided wound around a drive roll 22 and a support roll 24 that are in contact with the inner surface of the intermediate transfer belt 20, and runs in a direction from the first unit 10Y to the fourth unit 10K. A force is applied to the support roll 24 by a spring or the like (not shown) in a direction away from the drive roll 22, and tension is applied to the intermediate transfer belt 20 wound around them. An intermediate transfer belt cleaning device 30 is provided on the image bearing surface side of the intermediate transfer belt 20, facing the drive roll 22.
[0182] The developing devices (an example of developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with yellow, magenta, cyan, and black toners contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.
[0183] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative.
[0184] The first unit 10Y has a photoconductor 1Y. Around the photoconductor 1Y, there is a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, Arranged in this order are an exposure device (an example of an electrostatic image forming means) 3 that exposes the surface of the photoconductor 1Y to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a development device (an example of a development means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll (an example of a primary transfer means) 5Y that transfers the developed toner image onto the intermediate transfer belt 20, and a photoconductor cleaning device 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer.
[0185] The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20 and is provided at a position facing the photoconductor 1Y. A bias power supply (not shown) that applies a primary transfer bias is connected to the primary transfer rolls 5Y, 5M, 5C, and 5K of each unit.
[0186] The belt unit 60 is a belt unit equipped with the transfer opposing belt 50. The belt unit 60 includes the transfer opposing belt 50, a drive roll 62, and a support roll 64. The belt unit 60 is disposed outside the intermediate transfer belt 20, and is provided at a position facing the support roll 24. A bias power supply (not shown) that applies a secondary transfer bias is connected to the belt unit 60.
[0187] A transfer opposing belt cleaning blade 66 is provided on the transfer opposing belt 50 of the belt unit 60 in a freely contactable and detachable manner to remove residual toner and paper dust from the transfer opposing belt 50 after secondary transfer and to clean the outer peripheral surface of the transfer opposing belt 50.
[0188] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity of 1×10 at 20° C.-6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam, the resistivity of the portion irradiated with the laser beam changes. Therefore, the exposed surface of the charged photoreceptor 1Y is irradiated with a laser beam 3Y from the exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0189] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y rotates to a predetermined developing position as the photoconductor 1Y travels. At this developing position, the electrostatic image on the photoconductor 1Y is developed into a toner image by the developing device 4Y and made visible.
[0190] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.
[0191] When the yellow toner image on the photoconductor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoconductor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoconductor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y.
[0192] The primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K in the second unit 10M and subsequent units is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of each color are transferred and superimposed.
[0193] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section made up of the intermediate transfer belt 20, a support roll 24, and a belt unit 60. Meanwhile, a recording paper (one example of a recording medium) P is fed at a predetermined timing into the gap between the belt unit 60 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.
[0194] The recording paper P onto which the toner image has been transferred is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P to form a fixed image. After the color image has been fixed, the recording paper P is conveyed toward a discharge portion, and a series of color image forming operations is completed.
[0195] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets and the like.
[0196] On the other hand, after the transfer to the recording paper P is completed, the residual toner remaining on the transfer opposing belt 50 is transported to the transfer opposing belt cleaning blade 66 as the transfer opposing belt 50 rotates, and is removed from the transfer opposing belt 50 by the transfer opposing belt cleaning blade 66.
[0197] Although the present embodiment has been described above, the present invention is not limited to the above embodiment, and various modifications, changes, and improvements are possible. EXAMPLES
[0198] Hereinafter, examples of the present disclosure will be described, but the present disclosure is not limited to the following examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0199] Example 1 <Preparation of electrostatic image developer> -Preparation of amorphous polyester resin dispersion- (Preparation of polyester resin dispersion (APE1)) Terephthalic acid: 30 parts by mole Fumaric acid: 70 parts by mole Bisphenol A ethylene oxide adduct: 5 parts by mole Bisphenol A propylene oxide adduct: 95 parts by mole The above materials were charged into a 5-liter flask equipped with a stirrer, nitrogen inlet tube, temperature sensor, and distillation column, and the temperature was raised to 210°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature was raised to 230°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at that temperature for 1 hour, after which the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,500, an acid value of 14 mgKOH / g, and a glass transition temperature of 59°C was synthesized.
[0200] 40 parts of ethyl acetate and 25 parts of 2-butanol were added to a vessel equipped with a temperature control means and a nitrogen replacement means to prepare a mixed solvent, after which 100 parts of polyester resin were gradually added and dissolved, and a 10% by mass aqueous ammonia solution (equivalent to 3 times the molar amount of the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the container was replaced with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped at a rate of 2 parts / min while stirring the mixture, to perform emulsification. After the dropwise addition was completed, the emulsion was returned to room temperature (20°C to 25°C), and dry nitrogen was bubbled for 48 hours while stirring to reduce ethyl acetate and 2-butanol to 1,000 ppm or less, and a resin particle dispersion in which resin particles having a volume average particle size of 200 nm were dispersed was obtained. Ion-exchanged water was added to the resin particle dispersion to adjust the solid content to 20 mass%, to obtain a polyester resin particle dispersion (APE1).
[0201] -Preparation of colorant particle dispersion- (Preparation of Colorant Particle Dispersion (Black Pigment Dispersion)) Carbon black (Cabot, Regal 330): 250 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen SC): 33 parts (60% active ingredient, 8% colorant) -Ion-exchanged water: 750 parts 280 parts of ion-exchanged water and 33 parts of anionic surfactant were placed in a stainless steel container of a size such that the height of the liquid surface would be about 1 / 3 of the height of the container when all of the above components were added, and after the surfactant was sufficiently dissolved, all of the solid solution pigment was added and stirred with a stirrer until there was no unwetted pigment, and the mixture was sufficiently defoamed. After defoaming, the remaining ion-exchanged water was added, and the mixture was dispersed for 10 minutes at 5000 rpm using a homogenizer (IKA Ultra Turrax T50), and then defoamed by stirring with a stirrer for 1 day and night. After defoaming, the mixture was dispersed again for 10 minutes at 6000 rpm using a homogenizer, and then defoamed by stirring with a stirrer for 1 day and night. Subsequently, the dispersion was dispersed at a pressure of 240 MPa using a high-pressure impact disperser Ultimizer (Sugino Machine Co., Ltd., HJP30006). Dispersion was performed for 25 passes, calculated from the total amount charged and the processing capacity of the device. The resulting dispersion was left to stand for 72 hours to remove the precipitate, and ion-exchanged water was added to adjust the solid content to 15%, to obtain a colorant particle dispersion. The volume average particle size D50 of the particles in this colorant particle dispersion was 135 nm.
[0202] -Preparation of release agent dispersion- (Preparation of release agent dispersion (WAX1)) Paraffin wax (HNP9 made by Nippon Seiro, melting temperature 75℃): 270 parts Anionic surfactant (Dai-ichi Kogyo Seiyaku Co., Ltd., Neogen RK, active ingredient amount: 60%): 13.5 parts (as an active ingredient, 3.0% relative to the release agent) Ion-exchanged water: 21.6 parts The above components were mixed and the release agent was dissolved in a pressure discharge homogenizer (Gaulin homogenizer, manufactured by Gaulin Co., Ltd.) at an internal liquid temperature of 120°C. The mixture was then dispersed at a dispersion pressure of 5 MPa for 120 minutes, then at 40 MPa for 360 minutes, and cooled to obtain a release agent dispersion (WAX1). The volume average particle size D50 of the particles in this release agent dispersion (WAX1) was 225 nm. Ion-exchanged water was then added to adjust the solid content to 20.0%.
[0203] -Preparation of mixed particle dispersion- (Preparation of mixed particle dispersion (RW1)) 150 parts of polyester resin particle dispersion (APE1), 20 parts of release agent particle dispersion (WAX1), and 2.9 parts of anionic surfactant (Dowfax2A1 manufactured by The Dow Chemical Company) were mixed, and then 1.0% nitric acid was added at a temperature of 25°C to adjust the pH to 3.0, to obtain a mixed particle dispersion (RW1).
[0204] - Toner preparation - Polyester resin particle dispersion (APE1): 700 parts Colorant particle dispersion: 133 parts Ion-exchanged water: 400 parts Anionic surfactant (Dowfax2A1, manufactured by The Dow Chemical Company): 2.9 parts The above components were placed in a 3-liter reaction vessel equipped with a thermometer, a pH meter, and a stirrer, and 1.0% nitric acid was added at 25° C. to adjust the pH to 3.0. The mixture was then dispersed at 5,000 rpm with a homogenizer (Ultra Turrax T50, manufactured by IKA Japan Co., Ltd.) while 130 parts of the prepared aqueous aluminum sulfate solution was added and dispersed for 6 minutes.
[0205] Then, a stirrer and a mantle heater were installed in the reaction vessel, and the rotation speed of the stirrer was adjusted so that the slurry was sufficiently stirred. The temperature was raised at a rate of 0.2°C / min up to 40°C, and at a rate of 0.05°C / min after exceeding 40°C, and the particle size was measured every 10 minutes using a Multisizer II (aperture diameter: 50μm, manufactured by Coulter). When the volume average particle size reached 5.0μm, the temperature was maintained, and 450 parts of the mixed particle dispersion (RW1) were added over 5 minutes. After maintaining for 30 minutes, the pH was adjusted to 9.0 using a 1% aqueous sodium hydroxide solution. Thereafter, the temperature was raised to 85°C at a rate of 1°C / min and maintained at that temperature, while adjusting the pH to 9.0 every 5°C. When the particle shape and surface properties were observed using an optical microscope and a scanning electron microscope (FE-SEM), the coalescence of the particles was confirmed at the 5.0th hour, so the vessel was cooled to 30°C over 5 minutes with cooling water.
[0206] The cooled slurry was passed through a nylon mesh with 15 μm openings to remove coarse powder, and the toner slurry that passed through the mesh was filtered under reduced pressure with an aspirator. The toner remaining on the filter paper was crushed finely by hand and added to ion-exchanged water with a temperature of 30° C. and 10 times the amount of the toner, and mixed and stirred for 30 minutes. The mixture was then filtered under reduced pressure with an aspirator, and the toner remaining on the filter paper was crushed finely by hand and added to ion-exchanged water with a temperature of 30° C. and 10 times the amount of the toner, and mixed and stirred for 30 minutes, and then filtered under reduced pressure with an aspirator again, and the electrical conductivity of the filtrate was measured. This operation was repeated until the electrical conductivity of the filtrate was 10 μS / cm or less, and the toner was washed. The washed toner was crushed finely with a wet-dry type granulator (Comil), and then vacuum-dried in an oven at 35° C. for 36 hours to obtain toner particles.
[0207] Then, 3.3 parts of silica particles were added as an external additive to 100 parts of toner particles. The mixture was then mixed for 3 minutes at a peripheral speed of 30 m / s using a Henschel mixer. The mixture was then sieved using a vibrating sieve with an opening of 45 μm to obtain a toner.
[0208] -Creating the carrier- 500 parts of spherical magnetite particle powder having a volume average particle size of 0.18 μm was put into a Henschel mixer and thoroughly stirred, after which 5 parts of a titanate coupling agent was added, the temperature was raised to 95° C., and the mixture was mixed and stirred for 30 minutes to obtain spherical magnetite particles coated with a titanate coupling agent. Next, 6 parts of phenol, 10 parts of 30% formalin, 500 parts of magnetite particles, 7 parts of 25% aqueous ammonia, and 400 parts of water were added to a 1L four-neck flask and mixed and stirred. Next, the mixture was heated to 90°C over 60 minutes while stirring, reacted at the same temperature for 180 minutes, cooled to 30°C, added with 500ml of water, removed the supernatant, and washed the precipitate with water. This was dried at 180°C under reduced pressure, and coarse powder was removed using a sieve with a mesh size of 106μm to obtain core particles with an average particle size of 38μm. Next, 200 parts of toluene and 35 parts of a styrene-methyl methacrylate copolymer (component molar ratio 10:90, weight average molecular weight 160,000) were stirred with a stirrer for 90 minutes to obtain a coating resin solution. 1000 parts of core particles and 70 parts of coating resin solution were placed in a vacuum degassing kneader coater (rotor-wall clearance 35 mm) and stirred at 30 rpm for 30 minutes while maintaining the temperature at 65°C. The temperature was then lowered to 88°C, and the mixture was depressurized to remove toluene, degass, and dried. The mixture was then passed through a mesh with 75 μm openings. The shape factor SF2 of the carrier was 104.
[0209] - Preparation of developer - A developer was prepared by mixing 8 parts of the toner and 100 parts of the carrier in a V blender.
[0210] - Toner properties - The ratio of the release agent present in the region within 800 nm from the surface of the toner particles to the release agent in the entire toner particles (surface layer ratio of the release agent) was measured by the above-mentioned method. Also, the melting temperature of the release agent was measured by the above-mentioned method.
[0211] <Cleaning Blade Production> 100 parts by mass of polycaprolactone polyol (molecular weight 2000) as a high molecular weight polyol component and 58 parts by mass of 4,4'-diphenylmethane diisocyanate (MDI: manufactured by DIC Corporation) as a polyisocyanate component were reacted at 115°C for 20 minutes. Then, 6.1 parts by mass of 1,4-butanediol and 2.6 parts by mass of trimethylolpropane as low molecular weight polyol components were mixed and heat cured for 40 minutes in a mold maintained at 140°C. After molding, the rubber elastic body was cut into a width of 14 mm, a thickness of 1.9 mm, and a length of 330 mm, and this rubber elastic body was bonded to a support plate to form a blade substrate.
[0212] A surface treatment liquid was obtained by dispersing and mixing 80 parts by mass of ethyl acetate as an organic solvent, 25 parts by mass of 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by Tosoh Corporation, melting point: 38°C) as an isocyanate compound, and 5 parts by mass of a silicone-modified acrylic polymer (8BS-9000; manufactured by Taisei Fine Chemical Co., Ltd.) as an acrylic polymer having a siloxane bond, which is a specific polymer, in a ball mill for 5 hours.
[0213] The blade substrate was immersed in the surface treatment liquid for 60 seconds while keeping the surface treatment liquid at 23° C., and then dried for 1 minute in a room temperature (25° C.) environment. Next, the surface of the dried blade substrate was wiped with a sponge containing a small amount of toluene, further dried for 1 minute in a 25° C. environment, and heated for 50 minutes in an oven kept at 25° C. to obtain a cleaning blade.
[0214] -Cleaning blade properties- The ratio of the total amount of F and Si present within 200 nm of the surface of the cleaning blade that comes into contact with the transfer belt to the total amount of F and Si present within 5 μm of the surface (surface ratio of F, Si), the total amount of F and Si present on the surface that comes into contact with the transfer belt (surface F, Si amount (atm %)), and the total amount of F and Si present at a position 50 nm from the surface that comes into contact with the transfer belt (50 nm position F, Si amount (atm %)) were measured by the above-mentioned method.
[0215] <Preparation of Transfer Belt> -Preparation of conductive elastic layer A conductive rubber material containing carbon black in chloroprene rubber and ethylene propylene diene rubber was mixed, extruded with a kneading extruder, and dried with hot air to obtain a tubular body with a diameter (outer diameter) of 40 mm and an average thickness of 450 μm. The tubular body was cut to a length of 355 mm to form a substrate (conductive elastic layer).
[0216] Preparation of the surface layer A coating solution was prepared by adding 1% by mass of a curing agent (Loctite WH-1, Henkel Japan) to a urethane resin containing PTFE (polytetrafluoroethylene) particles (Bonderite T862A, Henkel Japan, PTFE content 65% by mass), and diluting with water. The coating liquid was sprayed onto the outer peripheral surface of the substrate while rotating the substrate with the central axis of the substrate in the horizontal direction. Then, hot air drying was performed at a temperature of 150° C. for 35 minutes to form a surface layer with an average thickness of 10 μm on the outer peripheral surface of the substrate. Next, the same coating liquid was sprayed onto the inner peripheral surface of the substrate, and hot air drying was performed in the same manner to form a surface layer with an average thickness of 10 μm on the inner peripheral surface of the substrate. In this way, a transfer facing belt having surface layers on both sides of the substrate (conductive elastic layer) was obtained.
[0217] <Image forming device> The electrostatic image developer, the transfer belt (the belt that contacts the surface of the recording medium opposite to the surface to which the toner image is transferred) and the cleaning blade for the transfer belt obtained above were attached to an image forming apparatus "FUJIFILM Business Innovation Co., Ltd. Versant 3100i Press." The attachment conditions for the cleaning blade for the transfer belt were set as follows: pressing pressure NF (Normal Force, gf / mm) was set to the conditions shown in Table 1, and the angle W / A (Working Angle) was set to 10°.
[0218] [Examples 2 to 12, Comparative Examples 1 to 5] <Preparation of electrostatic image developer> In Example 1, a release agent used in preparing the release agent dispersion was selected, and the amount of the mixed particle dispersion (RW1) used in preparing the toner was adjusted to prepare toner particles that satisfied the "surface layer ratio (%) of the release agent" and "melting temperature (°C) of the release agent" shown in Tables 1 and 2, and an electrostatic image developer was obtained. The following waxes were used as release agents having the melting temperatures shown in Tables 1 and 2, and the desired melting temperature was adjusted by using these waxes alone or in any desired ratio. Paraffin wax (manufactured by Nippon Seiro Co., Ltd., melting temperature 64°C) Paraffin wax (HNP9 manufactured by Nippon Seiro Co., Ltd., melting temperature 75°C) Ester wax (NOF Corp., melting temperature 82°C) Fischer-Tropsch wax (Nippon Seiro Co., Ltd., FNP-0090, melting temperature 90°C)
[0219] <Cleaning Blade Production> In Example 1, the amount of 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by Tosoh Corporation, melting point: 38°C) used in forming the cleaning blade was adjusted, and the composition of the surface treatment liquid used in the surface modification treatment of the contact area of the obtained blade substrate and the conditions of the surface heat treatment were changed to produce a cleaning blade that satisfies the "surface ratio of F,Si (%)", "surface F,Si amount (atm%)", "F,Si amount at 50 nm position (atm%)", and "100% modulus (MPa)" listed in Table 2. When the "silicone polymer" in Tables 1 and 2 was used as the surface treatment liquid, a treatment liquid was used in which ethyl acetate, 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by Tosoh Corporation, melting point: 38°C) as an isocyanate compound, and silicone-modified acrylic polymer (8BS-9000; manufactured by Taisei Fine Chemical Co., Ltd.) as an acrylic polymer having a siloxane bond were mixed. On the other hand, when the "fluorine compound" in Tables 1 and 2 was used, a treatment liquid in which fluorine silicone-modified acrylic polymer (8FS-009; manufactured by Taisei Fine Chemical Co., Ltd.) was mixed instead of the silicone-modified acrylic polymer (8BS-9000) was used.
[0220] <Preparation of Transfer Belt> In Example 1, the conductive particles used in producing the base material (conductive elastic layer) were changed to those shown in Tables 1 and 2, and a transfer opposing belt was obtained. Carbon black (Mitsubishi Chemical, #3230B) Tin oxide (Showa Kako, stannous oxide) Zinc oxide (Teika, MZ-300)
[0221] <Evaluation test> (1) Slipping through Using the image forming apparatus prepared in each example and comparative example, 10,000 images were output in an environment of 10°C temperature and 20% RH, and then a blank image (i.e., an image with 0% image density) was output and evaluated according to the following criteria. G0: No streaks G1: 3 or less mild streaks visible under a microscope (not visible to the naked eye) G2: More than three mild streaks visible under a microscope (not visible to the naked eye) G3: 3 or less minor lines visible to the naked eye G4: More than three visible minor lines G5: Clear lines appear
[0222] (2) Filming Using the image forming apparatus prepared in each Example and Comparative Example, 1,000 images were output in an environment of 28°C temperature and 80% RH, and then a 100 μm square image of the observation image of the transfer belt surface was binarized, the area ratio occupied by the adhesions was determined, and the image was evaluated according to the following criteria. G0: No adhesion (0% adhesion) G1: Slight adhesion (adhesion rate less than 1%) G2: Deposit ratio 1% to less than 3% G3: Deposit ratio 3% to less than 5% G4: Deposit ratio 5% to less than 10% G5: Deposit rate 10% or more
[0223] (3) Wear Using the image forming apparatus prepared in each Example and Comparative Example, 10,000 images were output in an environment of 28° C. temperature and 80% RH, and then the wear depth of the cleaning blade was measured and evaluated according to the following criteria. G0: No wear G1: Minor wear (wear depth is greater than 0 μm and less than 0.2 μm) G2: Wear depth is 0.2 μm or more and less than 0.4 μm G3: Wear depth is 0.4 μm or more and less than 1.0 μm G4: Wear depth is 1.0 μm or more and less than 2.0 μm G5: Wear depth 2.0μm or more
[0224] (4) Chipping A transfer belt having protrusions of 5 μm in height and 20 μm in width on its outer circumferential surface was prepared for the chipping evaluation test. This transfer belt was attached to the image forming apparatus prepared in each Example and Comparative Example, and 100 sheets of images were output in an environment of a temperature of 10° C. and a humidity of 20% RH. After that, the wear depth of the cleaning blade at the position corresponding to the protrusion was measured and evaluated according to the following criteria. G0: No chipping G1: Minor chipping (chip depth is greater than 0 μm and less than 1 μm) G2: Chipping depth is 1 μm or more and less than 2 μm G3: Chipping depth is 2μm or more and less than 4μm G4: Chipping depth is 4μm or more and less than 6μm G5: Chipping depth is 6μm or more
[0225] [Table 1]
[0226] [Table 2]
[0227] As shown in Tables 1 and 2, the image forming apparatus of this embodiment suppresses the occurrence of toner filming on the surface of the transfer belt and suppresses wear on the cleaning blade compared to the comparative example.
[0228] The present embodiment includes the following aspects. (((1))) An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; a transfer means having a transfer facing belt in contact with a surface of a recording medium opposite to a surface onto which the toner image is transferred, and transferring the toner image formed on the surface of the image carrier onto the surface of the recording medium; a cleaning device having a cleaning blade which comes into contact with the outer peripheral surface of the transfer opposing belt to clean the outer peripheral surface, the cleaning blade being made of polyurethane resin, the indentation elasticity of the surface which comes into contact with the transfer opposing belt being 15 MPa or more and 35 MPa or less, and the total amount of F and Si present within 200 nm from the surface which comes into contact with the transfer opposing belt being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising: (((2))) The image forming apparatus according to (((1))), wherein the amount of the release agent present in a region within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle. (((3))) The image forming apparatus according to (((1))) or (((2))), wherein the melting temperature of the release agent is 70° C. or higher and 75° C. or lower. (((4))) The image forming apparatus according to any one of (((1))) to (((3))), wherein the indentation elasticity of the cleaning blade is 20 MPa or more and 30 MPa or less. (((5))) The image forming apparatus of any one of (((1))) to (((4))), wherein the total amount of F and Si present within 200 nm from the surface of the cleaning blade that contacts the transfer opposing belt accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface. (((6))) The image forming apparatus according to any one of (((1))) to (((5))), wherein the cleaning blade has a surface that comes into contact with the transfer opposing belt and the total amount of F and Si present thereon is 15 atm % or more. (((7))) The image forming apparatus according to (((6))), wherein the cleaning blade has a surface that comes into contact with the transfer opposing belt and a total amount of F and Si present thereon of 18 atm % or more and 25 atm % or less. (((8))) The image forming apparatus according to any one of (((1))) to (((7))), wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the transfer opposing belt of 0.3 atm % or more. (((9))) The image forming apparatus according to (((8))), wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the transfer opposing belt of 0.3 atm % or more and 2.0 atm % or less. (((10))) The image forming apparatus according to any one of (((1))) to (((9))), wherein the cleaning blade contains a silicone-based polymer in a surface layer that comes into contact with the transfer opposing belt. (((11))) The image forming apparatus according to any one of (((1))) to (((10))), wherein the cleaning blade comes into contact with the transfer opposing belt with a pressing pressure of 1.5 gf / mm or more and 3.5 gf / mm or less. (((12))) The image forming apparatus according to any one of (((1))) to (((11))), wherein the transfer opposing belt has a conductive elastic layer containing carbon black, and a surface layer containing 35 mass % or more of polytetrafluoroethylene particles. (((13))) a charging step of charging a surface of an image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of transferring the toner image formed on the surface of the image carrier onto the surface of the recording medium by contacting a transfer opposing belt with a surface of the recording medium opposite to the surface onto which the toner image is transferred; a cleaning step of contacting an outer peripheral surface of the transfer opposing belt with a cleaning blade made of polyurethane resin, having an indentation elastic modulus of 15 to 35 at a surface in contact with the transfer opposing belt, and having a total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing belt that accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising:
[0229] According to the invention related to (((1))), an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the indentation elasticity modulus on the surface in contact with the transfer opposing belt exceeds 35 MPa, or in which the total amount of F and Si present within 200 nm of the surface in contact with the transfer opposing belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. According to the invention related to (((2))), an image forming apparatus is provided which has excellent low-temperature fixing ability of images compared to an image forming apparatus in which the release agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle. According to the invention related to (((3))), an image forming apparatus is provided which is superior in low-temperature image fixing ability compared to an image forming apparatus in which the melting temperature of the release agent is higher than 75°C, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed compared to an image forming apparatus in which the melting temperature of the release agent is lower than 70°C. According to the invention related to (((4))), an image forming apparatus is provided in which the occurrence of toner slip-through at the contact point between the transfer opposing belt and the cleaning blade is suppressed compared to an image forming apparatus in which the indentation elasticity modulus of the cleaning blade is less than 20 MPa, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed compared to an image forming apparatus in which the indentation elasticity modulus of the cleaning blade is more than 30 MPa. According to the invention related to (((5))), there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface that contacts the transfer opposing belt is less than 85% of the total amount of F and Si present within 5 μm from the surface. According to the invention related to (((6))) or (((7))), there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present on the surface that contacts the transfer belt is less than 15 atm %. According to the invention related to (((8))) or (((9))), there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed over time, as compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface that contacts the transfer belt is less than 0.3 atm %. According to the invention pertaining to (((10))), there is provided an image forming apparatus in which the surface layer that contacts the transfer belt does not contain a silicone-based polymer, and in which wear at the contact portion of the cleaning blade is suppressed compared to an image forming apparatus equipped with a cleaning blade that contains a fluorine-based compound. According to the invention pertaining to (((11))), an image forming apparatus is provided in which the occurrence of toner slip-through at the contact point between the transfer opposing belt and the cleaning blade is suppressed compared to an image forming apparatus in which the cleaning blade contacts the transfer opposing belt with a pressing pressure of less than 1.5 gf / mm, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the transfer opposing belt is further suppressed compared to an image forming apparatus in which the cleaning blade contacts the transfer opposing belt with a pressing pressure of more than 3.5 gf / mm. According to the invention pertaining to (((12))), there is provided an image forming apparatus in which the occurrence of toner slip-through at the contact point between the transfer opposing belt and the cleaning blade is suppressed, as compared to an image forming apparatus in which the transfer opposing belt has a conductive elastic layer that does not contain carbon black. According to the invention related to (((13))), there is provided an image forming method in which the occurrence of toner filming on the surface of the transfer opposing belt is suppressed and wear of the cleaning blade is suppressed, as compared to an image forming method having a cleaning step using a cleaning blade whose surface in contact with the transfer opposing belt has an indentation elasticity modulus of more than 35 MPa, or a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Explanation of symbols]
[0230] 1Y, 1M, 1C, 1K photoconductor 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor Cleaning Device 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 28 Fixing device (an example of fixing means) 30 Intermediate transfer belt cleaning device 50 Transfer belt 52 Base material layer 54 Protective layer 56 Protective layer 60 Belt unit 62 Driving Roll 64 Support Roll 66 Transfer belt cleaning blade P Recording paper (an example of a recording medium)
Claims
1. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; a transfer means having a transfer facing belt in contact with a surface of a recording medium opposite to a surface onto which the toner image is transferred, and transferring the toner image formed on the surface of the image carrier onto the surface of the recording medium; a cleaning device having a cleaning blade which comes into contact with an outer peripheral surface of the transfer opposing belt to clean the outer peripheral surface, the cleaning blade being made of polyurethane resin, the indentation elastic modulus of the surface which comes into contact with the transfer opposing belt being 15 MPa or more and 35 MPa or less, and the total amount of F and Si present within 200 nm from the surface which comes into contact with the transfer opposing belt being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising:
2. 2. The image forming apparatus according to claim 1, wherein the amount of the release agent present in a region within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle.
3. 2. The image forming apparatus according to claim 1, wherein the release agent has a melting temperature of 70[deg.] C. or higher and 75[deg.] C. or lower.
4. The image forming apparatus according to claim 1 , wherein the cleaning blade has an indentation elastic modulus of 20 MPa or more and 30 MPa or less.
5. 2. The image forming apparatus according to claim 1, wherein the total amount of F and Si present within 200 nm from the surface of the cleaning blade that contacts the transfer belt accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.
6. 2. The image forming apparatus according to claim 1, wherein the cleaning blade has a surface that comes into contact with the transfer belt, and the total amount of F and Si present on the surface of the cleaning blade is 15 atm % or more.
7. 7. The image forming apparatus according to claim 6, wherein the cleaning blade has a surface that comes into contact with the transfer belt, and the total amount of F and Si present on the surface is 18 atm % or more and 25 atm % or less.
8. 2. The image forming apparatus according to claim 1, wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the transfer opposing belt of 0.3 atm % or more.
9. 9. The image forming apparatus according to claim 8, wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the transfer opposing belt of 0.3 atm % or more and 2.0 atm % or less.
10. 2. The image forming apparatus according to claim 1, wherein the cleaning blade has a surface layer that contacts the transfer belt and contains a silicone-based polymer.
11. 2. The image forming apparatus according to claim 1, wherein the cleaning blade contacts the transfer belt with a pressing pressure of 1.5 gf / mm or more and 3.5 gf / mm or less.
12. 2. The image forming apparatus according to claim 1, wherein the transfer opposing belt has a conductive elastic layer containing carbon black, and a surface layer containing 35% by mass or more of polytetrafluoroethylene particles.
13. a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of transferring the toner image formed on the surface of the image carrier onto the surface of the recording medium by contacting a transfer opposing belt with a surface of the recording medium opposite to the surface onto which the toner image is transferred; a cleaning step of contacting an outer peripheral surface of the transfer opposing belt with a cleaning blade made of polyurethane resin, the indentation elasticity of the surface in contact with the transfer opposing belt being 15 to 35, and the total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing belt being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising:
Citation Information
Patent Citations
Cleaning blade
JP2001051565A